2004
DOI: 10.1074/jbc.m308644200
|View full text |Cite
|
Sign up to set email alerts
|

High Intensity ras Signaling Induces Premature Senescence by Activating p38 Pathway in Primary Human Fibroblasts

Abstract: Although oncogenic ras plays a pivotal role in neoplastic transformation, it triggers an anti-oncogenic defense mechanism known as premature senescence in normal cells. In this study, we investigated the induction of cellular responses by different expression levels of oncogenic ras in primary human fibroblasts. We found that a moderate, severalfold increase in ras expression promoted cell growth. Further elevation of ras expression initially enhanced proliferation but eventually induced p16INK4A expression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
140
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(147 citation statements)
references
References 52 publications
6
140
1
Order By: Relevance
“…The lack of involvement of p53 in BU-induced senescence prompted us to hypothesize that activation of the Erk-p38 MAPK pathway may mediate the induction, because activation of the Erk-p38 MAPK pathway has also been implicated in the induction of cellular senescence [13,15,34,35]. Indeed, it was found that treatment of WI38 cells with BU activated Erk and p38 in a time-dependent manner and inhibition of Erk or p38 with a specific inhibitor significantly suppressed BU-induced WI38 cell senescence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The lack of involvement of p53 in BU-induced senescence prompted us to hypothesize that activation of the Erk-p38 MAPK pathway may mediate the induction, because activation of the Erk-p38 MAPK pathway has also been implicated in the induction of cellular senescence [13,15,34,35]. Indeed, it was found that treatment of WI38 cells with BU activated Erk and p38 in a time-dependent manner and inhibition of Erk or p38 with a specific inhibitor significantly suppressed BU-induced WI38 cell senescence.…”
Section: Discussionmentioning
confidence: 99%
“…To elucidate the mechanisms of action whereby BU induces senescence, we first evaluated activation of the two key pathways that have been implicated in senescence induction: (1) the p53-p21 pathway triggered by DNA damage and (2) the p16-Rb pathway activated by the MAPK cascades [1,3,15,27]. The activation of these pathways was determined by analysis of phosphorylation of p53, Erk, p38, and JNK and expression of p21 and p16 using Western blot.…”
Section: Bu Induces Wi38 Cell Senescence Via the Erk-p38 Mapk Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…p16 INK4A promoter activity is enhanced by Ras and MKK6E It has previously been shown that p38 MAPK activation is necessary for Ras-induced senescence and that p38 MAPK activation is sufficient to induce senescence (Haq et al, 2002;Iwasa et al, 2003;Deng et al, 2004;Nelyudova et al, 2007;Kim et al, 2008). Our previous data revealed that HBP1 is a downstream effector of Ras, and p38 MAPK .…”
Section: Integrity Of Affinity Site Is Indispensable For Hbp1 Enhancimentioning
confidence: 99%
“…It confers cellular migration and invasion, but at the same time apoptosis (Haq et al, 2002;Deng et al, 2004;Behren et al, 2005;Qi et al, 2006;Sun et al, 2007). In this study we attempted to identify downstream regulators of this pathway that specifically convey signals culminating in an in vitro invasive phenotype.…”
Section: Introductionmentioning
confidence: 99%